MODEL PELAYANAN PENANGGULANGAN KEMISKINAN DI UNIT PELAYANAN TERPADU PENANGGULANGAN KEMISKINAN (UPT-PK) KABUPATEN SRAGEN - Jhody, Puguh Setyawan (Indonesian State Law Review (ISLRev), 2019)
The focus of research is on poverty reduction service models based on education, health, social economy, and data integration as well as implementation constraints. The study uses a qualitative legal research approach to the type of sociological juridical research using interactive analysis models analysis. The problem of poverty is a complex multidimensional as a general social phenomenon that requires countermeasures, systematic handling, integrated, comprehensive. These efforts are used to reduce the burden and fulfill the basic rights of citizens appropriately to create a prosperous community life. The current poverty reduction models tend to be off-target, convoluted bureaucracy, weak monitoring and evaluation, overlapping authority, and budget waste. Therefore, the Sragen Regency Government established the Poverty Reduction Service Unit (UPT-PK). The unit is a cross-sectoral integrated service unit in carrying out poverty reduction to simplify and facilitate the poor to access various government programs intended for them.  Poverty alleviation is the policy of the Sragen Regency Government in realizing community welfare.